2001
DOI: 10.1046/j.1440-1754.2001.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Ten years’ experience of persistent hyperinsulinaemic hypoglycaemia of infancy

Abstract: Persistent hyperinsulinaemic hypoglycaemia of infancy remains a major diagnostic and management challenge. Early suspicion and recognition is critical with definitive investigation and medical therapy to avoid hypoglycaemia, with pancreatectomy in medically unresponsive cases. Normal neurodevelopmental outcome was found in only 55% of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
14

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 38 publications
1
15
1
14
Order By: Relevance
“…Other studies have shown that only 20% of infants with hyperinsulinaemia are LGA at birth. 25 Our study supports the recent advice to refrain from routine blood glucose measurements in healthy term infants who are not small for gestational age. 9 Our study sample comprised infants born in hospital.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have shown that only 20% of infants with hyperinsulinaemia are LGA at birth. 25 Our study supports the recent advice to refrain from routine blood glucose measurements in healthy term infants who are not small for gestational age. 9 Our study sample comprised infants born in hospital.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, trends indicate an increased prevalence of developmental delay and psychomotor retardation in infants undergoing surgery at a later age [16,17] . The effi cient diagnosis and surgical management of HI in the present case stands in contrast to the variable time to diagnosis and surgery in other studies of HI (median: 1-180 days; median: 30-354 days, respectively) [3,11,12,14,[16][17][18][19][20] . The in utero diagnosis of HI in our case allowed for the immediate initiation of medical management at birth with a quicker progression to surgical management when medical management failed.…”
Section: Discussioncontrasting
confidence: 77%
“…Similarly, other studies have demonstrated an increased risk of persistent neurodevelopmental delays, reduced head circumference, reduced IQ scores and an increased rate of clinical complications at the time of birth associated with a delay in diagnosis and adequate management of hypoglycemia in the neonate [7][8][9][10] . Studies of infants with HI also indicate an increased incidence of neurodevelopmental problems associated with a delay in the recognition and management of hypoglycemia [1,[11][12][13][14][15] . This is exemplifi ed by the study of Jack et al [14], which supports improved neurodevelopmental outcomes in patients euglycemic within 35 days of presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, repeated episodes of severe, prolonged, sublethal hypoglycemia can result in permanent neurological damage, including developmental delay, mental retardation, and/or focal CNS deficits. Complications of neonatal hyperinsulinism are found in up to 50% of survivors, and this incidence has changed little during the past 20 years, reflecting the major problems that are faced in managing and treating this condition (5,8,9,29,166,173,181,196,201,253,284,313).…”
Section: Early Complications Of Hyperinsulinism In Infancymentioning
confidence: 99%